FENOMENA POLITISASI BIROKRASI DILIHAT DARI SUDUT PANDANG ADMINISTRASI PUBLIK (Studi pada Ketidaknetralan Aparatur Sipil Negara di Indonesia Saat Pemilu dan Pilkada): - , Muhammad Emir Al-Azkiya; S. Agus Santoso (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research aims to look at the phenomenon of bureaucratic politicians in Indonesia from a public administration perspective. The research method used by the researcher is qualitative research using the desk research method, where the research results obtained by the author are analyzed using the theory of bureaucratic political control. The results of this research show that bureaucratic politicization in Indonesia is often found during political contestation, namely general elections (Pemilu) and regional head elections (Pilkada). In the scientific scope of public administration, the dichotomy of politics and administration is proof that political and administrative issues cannot be combined. In the context of bureaucratic politicization, political and bureaucratic control should be able to protect State Civil Servants (ASNs) from violating ASN neutrality. Unfortunately, these ASN individuals are willing to sacrifice their integrity just to fulfill their personal interests rather than prioritizing the public interest, namely community satisfaction. Apart from that, the politicization of the bureaucracy will only hinder the ideals of the Indonesian bureaucracy, which prioritizes a merit system. To minimize bureaucratic politicization in Indonesia, several strengthening strategies are needed, such as (1) optimizing SBT (Integrated Sharing System), (2) strengthening relationships between interrelated stakeholders, (3) maximizing the role of whistleblowers in each agency and providing guarantees of protection, and (4) imposing strict sanctions.